Pengelolaan Pembelajaran Teknik Kendaraan Ringan Berbasis ISO Di SMK Muhammadiyah 2 Andong - SETYOKO, Heru, Prof. Dr. Sutama, M.Pd, Dr. H. Saminom, M.M (2015)
The purpose of this study was (1) to describe the learning plan based on ISO light vehicle engineering at SMK Muhammadiyah 2 Andong. (2) To describe the implementation of learning-based techniques ISO light vehicles in SMK Muhammadiyah 2 Andong. (3) To describe the evaluation of learning techniques based on ISO light vehicles in SMK Muhammadiyah 2 Andong. The research is a qualitative research design ethnography. The study was conducted at SMK Muhammadiyah 2 Andong Boyolali. Techniques of data collection with in-depth interviews, documentation and observation. Analysis of the data using the interactive model with three stages. The results of the study were (1) Planning learning techniques based on ISO light vehicles in SMK Muhammadiyah 2 Andong an administrative document learning (DAP), as a reference for implementing learning, compiled by the teacher prior to the implementation of learning activities based learning. Planning ISO always enhanced on an ongoing basis, to assess the competence and basic competences (SK. KD) preparing a syllabus, calculate Effective weeks, making half of the annual program to program, compose a new lesson plan. (2) The study emphasizes the process of formation of the student learning experience (learning experiences), conducted through face to face, emphasizing the process of formation of the student learning experience. Core learning activities carried out with an emphasis on the process of learning that high activity levels. Learning-oriented student activity penguasaana emphasis on knowledge, change attitudes and increase students' skills. (3) Evaluation of learning techniques based on ISO light vehicles in SMK Muhammadiyah 2 Andong includes daily tests, replicates the midterm (mid term), general tests or repeat block, which is held each semester, a special class XII in addition to the evaluation, students are required to take exams national. Evaluation is done outside of school do when students follow industry work practices (Prakerin), the implementation of the assessment carried out by the supervising teacher of the school or by the industry.